Pengaruh Disiplin Kerja , Komunikasi dan Pengawasan Kerja Terhadap Kinerja Karyawan pada PT. Berkah Sekawan Abadi (Fit Bsa) Tulungagung - KHOZIN, NUR (Jurnal Cendekia Manajemen (JCM); Vol 2 No 2 (2024): JulyDO - 10.32503/jcm.v2i2.6120, 2024)
This research discusses the influence of work discipline, communication and work supervision on employee performance at PT Berkah Sekawan Abadi (Fit Bsa) Tulungagung. The method used in this research is quantitative. The population in this study were all employees of PT Berkah Sekawan Abadi (FIT BSA) Tulungagung, totaling 34 employees. The sampling technique used is Census Sampling. Data analysis in this research uses Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression. Work discipline variables influence employee performance variables at PT Berkah Sekawan Abadi (FIT BSA) with a significance value of 0.006 < 0.05. Work communication variables influence employee performance variables at PT Berkah Sekawan Abadi (FIT BSA) with a significance value of 0.006 < 0.05. Work supervision influences employee performance variables at PT Berkah Sekawan Abadi (FIT BSA) with a significance value of 0.017 < 0.05. Communication discipline and work supervision have a simultaneous effect on employee performance at PT Berkah Sekawan Abadi (FIT BSA) Tulungagung with a significant value of 0.046 < 0.05.